STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMPERBAIKI AKHLAK SISWA DI SMAI AN NUURU TIRTOYUDO - Ridho Andi Fauzi; Muhammad Hanif; Moh. Eko Nasrullah (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Strategy is a planned step that contains a series of activities that have been designed in such a way by someone carefully tailored to the goals to be achieved. Islamic Religious Education Learning Strategies in fostering students' Akhlakul karimah are a series of activities that have been carefully designed by Islamic Religious Education learning to improve coaching, or actions to foster student morality in a particular school institution in accordance with the place where Islamic Religious Education is taught. Students who have good morals always show good behavior in relationships with God, relationships with others, relationships with the environment and relationships with themselves. The occurrence of moral degradation and the number of deviations committed by students is required for Islamic Religious Education learning strategies in conducting student moral development. Based on that, the researchers conducted research at SMAI An Nuuru Tirtoyudo with the title of learning strategies for Islamic religious education in improving students' morals.